The Potential of Shell Extract as a Hemostasis and Wound Healing Agent: A Literature Review - Erlyn, Putri; Irfannuddin, Irfannuddin; Murti, Krisna; Lesbani, Aldes (Fakultas Kedokteran Universitas Brawijaya, 2024)
Hemostasis is an emergency medical treatment to reduce pain and patient mortality, therefore research is being developed to find effective hemostasis. The utilization of natural materials for hemostasis and wound healing is rapidly expanding, including chitosan found in shell extracts. Chitosan is obtained from chitin found in the soft shells of marine animals such as squid, shrimp, and crabs, or from hard shells such as clams, crabs, and lobsters. Chitosan offers advantages such as good biodegradability, biocompatibility, and non-toxicity, and has been widely used in biomedical, chemical, food, and cosmetic industries. This literature review aims to investigate the potential of shell extracts, particularly the characteristics of chitosan, in wound healing across hemostasis, inflammation, proliferation, and remodeling stages. The study results indicate that extracts from shells containing chitosan exhibit varying characteristics in terms of molecular weight and degree of deacetylation. Chitosan with higher molecular weight and degree of deacetylation tends to yield better outcomes in hemostasis and wound healing. The material is effective in reducing antithrombin, enhancing blood clotting processes, and aiding clot formation. Increased molecular weight contributes to stimulating various cytokines, such as TNF-α, TGF-ß1, and FGF2, which play a key role in the wound healing process. Additionally, higher degree of deacetylation chitosan is effective in stimulating fibroblast proliferation. Chitosan also influences VEGF in inducing angiogenesis and enhancing neovascularization in bone healing. Chitosan from shell extracts with certain molecular weight characteristics and degree of deacetylation has the potential to be the material of choice for accelerating hemostasis and wound healing.